HAKIKAT PERKAWINAN DALAM PARADIGMA AL-QUR'AN - Maylissabet (An-Nawazil: Jurnal Hukum dan Syariah Kontemporer, 2023)
Abstract: Marriage is the beginning of the formation of a family. The good of a society, created because of the goodness of the family in it. A good family is a family that is in harmony with the paradigms of the Koran and Hadith. Guidelines regarding marriage in the Qur'an cover many aspects, starting from before marriage, during marriage, even after marriage. Therefore, to achieve the family desired by the Koran, people who are about to get married at least understand a number of things related to marriage. This includes understanding the principles of marriage, the purpose of marriage, the pillars and conditions for legal marriage and others. It is from here that the nature of marriage in the paradigm of the Qur'an will be realized in family life. As a result, the principles and objectives set out in Law No. 1 of 1974 concerning Marriage have attempted to realize the principles and objectives intended by the Qur'an and Hadith. This is evidenced by the many principles and objectives desired by the Qur'an and hadith which have also been described in the rules of Law No. 1 of 1974 concerning Marriage. Keywords: Paradigm, Nature, Marriage, Al-Qur'an Abstrak Perkawinan merupakan awal dari terbentuknya sebuah keluarga. Baiknya sebuah masyarakat, tercipta karena baiknya juga keluarga di dalamnya. Keluarga yang baik adalah keluarga yang selaras dengan pardigma al-Qur’an maupun Hadits. Pedoman mengenai perkawinan di dalam al-qur’an meliputi banyak aspek, mulai dari sebelum terjadinya perkawinan, ketika dalam perkawinan, bahkan sampai pasca perkawinan. Oleh karena itu, untuk mencapai keluarga yang diinginkan oleh alqur’an, maka orang yang akan menikah setidaknya paham beberapa hal terkait perkawinan. Hal itu diantaranya memahami, asas-asas perkawinan, tujuan perkawinan, rukun dan syarat sah perkawinan dan lain-lain. Dari sinilah hakikat perkawinan dalam paradigma al qur’an akan terealisasi dalam kehidupan keluarga. Hasilnya, asas dan tujuan yang dipaparkan dalam UU N0 1 Tahun 1974 tentang Perkawinan telah berusaha untuk mewujudkan asas dan tujuan yang dimaksudkan oleh al-Qur’an dan Hadits. Hal ini dibuktikan banyak asas-asas maupun tujuan yang diinginkan oleh al-Qur’an maupun hadits telah dipaparkan juga di dalam aturan UU N0 1 Tahun 1974 tentang Perkawinan Kata Kunci: Paradigma, Hakikat, Perkawinan, Al-Qur’an